Plasma K+ dynamics and implications during and following intense rowing exercise - Atanasovska, T.; Petersen, A. C.; Rouffet, D. M.; Billaut, F.; Ng, I.; McKenna, M. J. (Journal of Applied Physiology, 2014)
We investigated whether potassium (K+) disturbances during and following intense exercise may be pronounced when utilizing a large contracting muscle mass, examining maximal 2,000-m rowing exercise effects on radial arterial plasma K+ concentration ([K+]a) in 11 healthy adults. Blood was sampled at baseline, preexercise, each 30 s during rowing, and for 30 min postexercise. Time to complete 2,000 m was 7.26 ± 0.59 min; power output at 30 s was 326 ± 81 W (mean ± SD). With exercise time expressed in deciles, power output fell 16.5% from the first to fourth decile (P < 0.05) and 19.9% at the ninth decile (P < 0.05); EMG median frequency declined 4.6% by the third decile and 5.5% by the eighth decile (P < 0.05). Plasma [K+]a increased from 3.89 ± 0.13 mM at rest to 6.13 ± 0.46 mM by 90 s rowing (P < 0.001) and was then sustained until end exercise (P < 0.001). In recovery, [K+]a decreased abruptly, reaching 3.33 ± 0.22 mM at 5 min postexercise (P < 0.001) and remaining below preexercise after 30 min (P < 0.005). At end exercise, blood [lactate]a (preexercise 0.64 ± 0.18 mM) reached 10.87 ± 1.33 mM, plasma volume decreased 9.7 ± 2.3% from preexercise, and pHa decreased to 7.10 ± 0.07 units (P < 0.001). In conclusion, arterial hyperkalemia was sustained during exhaustive rowing reflecting a balance between K+ release and reuptake in contracting muscles and K+ uptake by inactive muscles. While high, the [K+]a was lower than anticipated compared with maximal cycling or sprinting, possibly reflecting greater adrenergic response and Na+,K+-ATPase activity in contracting muscles; fatigue was evidenced by reduced power output and EMG median frequency. A prolonged hypokalemia after rowing likely reflected continuing muscular Na+,K+-ATPase activity.